Strategi Pengembangan Heritage Tourism Di Kompleks Percandian Batujaya, Kabupaten Karawang, Jawa Barat - Anjani, Alifia; Suryasih, Ida Ayu; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
This study aims to analyze the existing conditions of the 4A tourism product components and examine the development strategy of heritage tourism in Batujaya Temple Complex. The research method used is qualitative descriptive with a SWOT analysis approach using the IFAS and EFAS matrices, Internal-External matrix, and SWOT analysis matrix. Data were collected through observation, interviews, and documentary study, using purposive sampling as the technique for selecting informants. The results of the study show that Batujaya Temple Complex offers attractions such as Candi Jiwa, Candi Blandongan, wells, unur-unur, and Batujaya Cultural Heritage Site Museum. The accessibility through roads is good, but there is no public transportation available. Amenities provided include an auditorium, mosque, toilets, gazebos, canteen, inter-temple connecting paths, and parking lots. However, there are deficiencies such as the absence of an information center, CCTV, insufficient toilets and gazebos, suboptimal inter-temple connecting paths, and limited parking space. The only ancillary service in the complex is the Caretaker. Other challenges include the lack of travel agencies and minimal participation of the local community due to the inactivity of the Pokdarwis (Tourism Awareness Group). The resulting development strategies include 4 SO (Strengths-Opportunities) strategies, 5 WO (WeaknessesOpportunities) strategies, 2 ST (Strengths-Threats) strategies, and 3 WT (Weaknesses-Threats) strategies. These strategies can be implemented through concrete steps such as establishing an information center, installing CCTV, adding toilets and gazebos, improving inter-temple connecting paths, expanding parking areas, enhancing promotion, collaborating with the private sector, revitalizing Pokdarwis, providing education and training to the local community, developing integrated tour packages, establishing public transportation, and planning tsunami mitigation measures. Keywords: heritage tourism, existing conditions, development strategy